Analisis Vibrating Sample Magnetometer (VSM) Pada Hasil Elektrodeposisi Lapisan Tipis MagnetiteMenggunakan Aruscontinue Direct Current - Tebriani, sylvina (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
A magnetite (Fe3O4) thin film was grown on the Indium Thin Oxide (ITO) substrate by the Electrodeposition (ED) method, using the Continue Direct Current (CDC). Characterization with VSM is done to obtain information about the magnitudes of magnetic properties as a result of changes in the external magnetic field depicted in the hysteresis curve. VSM characterization results showed that the electrodepositioned magnetite thin films were paramagnetic, both for electrolyte solutions without ethylene glycol and electrolyte solutions that were dropped by ethylene glycol. Based on the comparison of the hysterisis pattern between samples that were characterized without surfactants, or those added with 10% surfactant to their solvents, it was said that the addition of ethylene glycol to base solution, affected the response of the material to the given external magnetic field. Samples with surfactants 10% have a greater slope than samples without surfactants, in other words samples without surfactants (by heating) are faster magnetized compared to the addition of surfactants.